Numerical Investigation on Serpentine Flow Field and Rhombus Electrolyte Compartment of Vanadium Redox Flow Battery (V-RFB) - Khor, Ai Chia; Mohd Rusllim, Mohamed; M. H., Sulaiman; Hamdan, Daniyal; A. N., Oumer; P. K. , Leung (Asian Research Publishing Network (ARPN), 2016)
Selection of suitable material, fitting for prototype design and pumping rates are three affecting element for cost effectiveness and improve performance of vanadium cell prototype investigation. Therefore, three-dimensional numerical model isothermal computational fluid dynamics (CFD) model of vanadium redox flow battery (V-RFB) is studied. In this work, V-RFB with different electrolyte compartments is proposed and the effect of serpentine flow field is investigated. The performance of two V-RFBs with diamond and square electrolyte compartment is numerically tested. This work has been performed to optimize flow rate, electrolyte compartment design, avoid stagnant fluid and flow field application in VRFB. For the simulation, the flow was assumed to be incompressible, isothermal, steady state flow, laminar and Newtonian flow. Results show that the application of flow field and Rhombus type electrolyte compartment can facilitate the distribution of electrolyte in the unit cell uniformity and avoid stagnant in the tank. Simulation results indicate the diamond shape and serpentine flow field at optimal flow rate show the most suitable for V-RFBs than square shape.